1999
DOI: 10.1016/s0167-2789(99)00015-9
|View full text |Cite
|
Sign up to set email alerts
|

Macroscopic chaos in globally coupled maps

Abstract: We study the coherent dynamics of globally coupled maps showing macroscopic chaos. With this term we indicate the hydrodynamical-like irregular behaviour of some global observables, with typical times much longer than the times related to the evolution of the single (or microscopic) elements of the system. The usual Lyapunov exponent is not able to capture the essential features of this macroscopic phenomenon. Using the recently introduced notion of finite size Lyapunov exponent, we characterize, in a consiste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
54
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 23 publications
(66 reference statements)
2
54
0
Order By: Relevance
“…modes, which are delocalized over the collection of the dynamical units and thus exert relevant perturbations to macroscopic variables, without the need for finite-amplitude perturbations as opposed to some earlier claims [20,21]. The CLVs allow us to detect such collective modes with the delocalization criterion, Y (j) 2 ∼ 1/N, and to examine directly their role in the collective dynamics, as demonstrated for the regime of nontrivial collective chaos in globally-coupled limit-cycle oscillators (Section 2).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…modes, which are delocalized over the collection of the dynamical units and thus exert relevant perturbations to macroscopic variables, without the need for finite-amplitude perturbations as opposed to some earlier claims [20,21]. The CLVs allow us to detect such collective modes with the delocalization criterion, Y (j) 2 ∼ 1/N, and to examine directly their role in the collective dynamics, as demonstrated for the regime of nontrivial collective chaos in globally-coupled limit-cycle oscillators (Section 2).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 99%
“…The velocity (12) does not depend on the chosen threshold values [2,4,10]. Since the dynamics of the difference field (11) is not confined in the tangent space, non linearities can play a crucial role in the information propagation.…”
Section: Information Spreading In Spatially Distributed Systemsmentioning
confidence: 99%
“…Indeed, finite disturbances, which are not confined in the tangent space, but are governed by the complete nonlinear dynamics, play a fundamental role in the erratic behaviors observed in some high dimensional system [8][9][10][11][12]. A rather intriguing phenomenon, termed stable chaos, has been reported in [9]: the authors observed that even a linearly stable system (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we will mainly consider two quantities: the Finite-Size Lyapunov Exponent (FSLE) and -entropy. The former was introduced in the context of developed turbulence [Aurell et al, 1997] and has proven to be more suited for a broad range of systems where the dynamics exhibit low-dimensional chaotic behavior only on large-scale [Shibata & Kaneko, 1998;Cencini et al, 1999;Gao et al, 2006]. Roughly, if we want to quantify the sensitivity to initial conditions on large scales, it is necessary to consider perturbations which are not infinitesimal.…”
Section: Finite-size Lyapunov and -Entropymentioning
confidence: 99%
“…In an attempt to reconcile these observations, we rely on recently introduced generalization of classical nonlinear tools. In particular, Finite-Size Lyapunov Exponent [Aurell et al, 1997;Shibata & Kaneko, 1998;Cencini et al, 1999;Gao et al, 2006] and the -entropy [Cencini et al, 2000] have proven to be valuable measures to probe the system which displays different behaviors at different scales. In the present context, where low-dimensional dynamics can take place on top of a highly irregular neuronal behavior, those measures appear as the most natural.…”
Section: How To Reconcile These Data?mentioning
confidence: 99%